Wabo - A Halim, Muhammad Fahmi; Abdullah*, Muhammad Zulfahmi; Mohd Fuad, Mohd Fareed Daniel; Awang, Muhammad Izzat (Universiti Teknologi MARA, Kedah, 2018)
An application that can help students or users to search for their books. The application will show the directory to the book by scanning the call number or QR code. After scanning the QR code it will show the direction to the book.